Reporting guidelines for in-silico studies using finite element analysis in medicine (RIFEM). (April 2022) - Mathur, Vijay Prakash; Atif, Mohammad; Duggal, Isha; Tewari, Nitesh; Duggal, Ritu; Chawla, Anoop
Highlights: Finite element analysis has multitude of applications in biomechanics and biophysics to study the mechanical behaviour of tissues or organs. Inconsistencies in reporting such studies have been thereby affecting their reliability and reproducibility. We have developed standard reporting-guidelines for biomechanical studies to bring about a consistency in reporting such studies so that no significant information related to the FE model or FE analysis is missed. These reporting guidelines can help in improving the details of these studies so as to facilitate ease in understanding and extrapolation of the results in clinical scenario. Abstract: Background: To the best of our knowledge, there are no reporting guidelines for design, conduct and reporting of Finite Element studies in health sciences. We intend to propose specific and detailed guidelines for reporting these studies. Method: After recognizing the need to have uniform guidelines for reporting of finite element analysis in medicine and dentistry, a group of 5 researchers working on FEA as their research area met in the summer of 2020 and drafted the methodology for the development of such guidelines. Each researcher individually made a list of major headings required for reporting these studies and met again in September 2020 to finalize the domains. Subsequently, sub headings and details were charted. The draft list of items for reporting the guidelines were presented to a larger team of 15 experts and some changes were further made based on their inputs. Results: The guidelines entail seven major domains and their sub-domains, including parameters for model structure, segmentation, mesh structure, force application and model validation, etc. This checklist aims to improvise the reporting and consistency of FEA studies. Conclusion: We hope that the usage and adoption of these guidelines by the scientific community would result in more thoughtful and uniform documentation. Also, the confidence in the results would be enhanced through model reproducibility, reusability and accountability. The proposed guidelines were named as 'Reporting of in-silico studies using finite element analysis in medicine' and the term 'RIFEM' was used as acronym.